The Effect Of Dividend Policy, Leverage And Profitability On Company Value - Devi, Anjeli Seri; Matyani, Matyani; Sofyaun, Ashari (Universitas Syiah Kuala, 2025)
The purpose of this study is to determine the effect of Dividend Policy, Leverage and Profitability on Company Value in Mining Subsector Companies listed on the Indonesian Stock Exchange. In this study, there was a population of 24 companies and a sample of 19 companies taken with several criteria determined by the author. The method used in this study is a statistical test with secondary data taken from the company's financial statements for the period 2020 to 2023. The results of the study show that partially the dividend policy variable has a positive relationship direction and does not affect company value, while leverage has a negative relationship direction. and significant to company value, and profitability has a positive relationship direction and has a significant influence on company value.